The role of the Barbarossa brothers in extending the Ottoman influence in the central Maghreb (Algeria) (916-953 AH / 1510-1546 AD) - Abu Nahel, Osama Mohammed (Journal of Humanities & Social Sciences, 2023)
The study dealt with the state of weakness and disintegration that prevailed in the countries of the Islamic Maghreb in general, and the central Maghreb region (Algeria) in particular, which led the Portuguese and Spanish to take advantage of the opportunity to occupy a large number of its cities. Meanwhile, with the help of the Ottoman Sultanate, the phenomenon of Islamic maritime jihad emerged in the western basin of the Mediterranean and in the central Maghreb, which aimed to help the Muslims of Andalusia fleeing their religion from the persecution of the Spanish on the one hand and worked to liberate the cities of the central Maghreb which the Spanish had occupied on the eve of and after the fall of Granada on the other hand. This task was undertaken by the two brothers Arouj and Khairuddin Barbarossa, who were able to perform it with unparalleled success, so they saved the cities of central Maghreb from the clutches of the Spanish. Khairuddin took the city of Algeria as the capital of his rule and didn’t hesitate to include this region in the possessions of the Ottoman Sultanate, and it now bears the name of the Viceroyalty of Algeria. The study relied on two main approaches: the historical approach and the analytical descriptive approach. It also reached a number of results, the most important of which are: that the Barbarossa brothers ruled Algeria direct delegation from the Ottoman Sultan, and became ministers of delegation with the approval of the Ottoman Sultanate. Thus: The new military state established in Algeria was a self-governing authority closely linked to the central government in Istanbul.